PENGARUH PEMBERIAN TERAPI BEDAK HERBAL TERHADAP PENURUNAN SUHU PADA BAYI DEMAM PASCA IMUNISASI - Kasmiati Kasmiati; Nurhaeda Nurhaeda (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Introduction: An efective form of health intervention in reducing infant and toddler mortality rates is immunization. ane of the routine immunizations give at he age 11 months is the DPR-HB-Hib Imunization which is the basic imunization which is the Immunization for babies. Adverse evenths after DPT imunization, namely local reactions of redness, swelling and pain at the injection site, occurred in half of DPT recipients, seizures, fever. Fever is treated with antipyretic drugs. Apart from antipyretics, lowering the temperature can be done by Using Tradisonal medicine Methods: The research design used pre-experimental design, pre-test and post test design. using one grup, namely assessing pre-test and post-test population used all infants following immunization Sampel of this study, infants who have met the criteria, were selected based on purposive sampling method. Results: The results of the Characteristic Test of the majority of respondents aged 4 months were 27 Pople (46,5%), while the amallest respondents aged 2 months were 12 pople (20,7%), age 3 mouthe were 19 pople (32,8%), From the resulth of the paired t-statistical test, it was concluded that 58 babies in the pretest group with a mean of 37,76 and in the postest group after Giving herbal powder there was a change in the form of a decrease in body temperature, mean 37,17 with a p value of 0,000 (p<0,05). Conclusion: Herbal powder therapy on reducing the temperature of infant fever after immunization. Therefore, reducing body temperature can be done physically (nonpharmacology), namely the use of traditional medicine.  Keywords: Post-immunization febrile in infants, Herbal powder, Temperature reduction